Transcatheter balloon dilation for recurrent right ventricular outflow tract obstruction following valve‐sparing repair of tetralogy of Fallot. Issue 4 (24th April 2015) - Gellis, Laura; Banka, Puja; Marshall, Audrey; Emani, Sitaram; Porras, Diego
<x xml:space="preserve">Abstract</x> Background Valve‐sparing repair in patients with tetralogy of Fallot (TOF) carries the risk of residual or recurrent right ventricular outflow tract (RVOT) obstruction, which is often treated with transcatheter balloon dilation (BD). The outcomes and associated complications of BD of the RVOT in this scenario remain unknown. Methods Retrospective review of the records of the Department of Cardiology at Boston Children's Hospital from 2000 to 2013 was performed. Results 34 patients had initial valve‐sparing repair of tetralogy of Fallot followed by BD of the RVOT during the study period. Following BD, the RVOT gradient decreased from a median of 43 mm Hg (range 13 to 79 mm Hg) to 28 mm Hg (range 0 to 73 mm Hg) (P < 0.001). Freedom from reintervention was 64% at 1 year and 46% at 3 years. Trivial to mild PR pre‐BD was present in 56% (n = 19) of patients and decreased to 37% (n = 11) post‐BD. Exclusively valvar obstruction was associated with a longer freedom from reintervention (P = 0.05), while a ratio of RV pressure to aortic systolic pressure pre‐BD of >1 and a final RVOT gradient of ≥40 post‐BD were associated with shorter freedom from reintervention (P < 0.001). Conclusion BD in patients with recurrent RVOT obstruction following valve‐sparing repair of TOF acutely reduces the RVOT gradient, but commonly results in increased PR and is associated with a high reintervention rate. Patients with stenosis solely at the level of the valve had a better response to this type of intervention. © 2015 Wiley Periodicals, Inc.